INOVASI SISTEM PEMBELAJARAN TEMATIK INTEGRATIF BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN EFEKTIF DI SEKOLAH DASAR - Nurmawati, Fulusia; Maysaroh, Luluk; Anindia Hizraini, Ayu (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
The development of models in the era of digitalization has become an important part of the education sector. The urgency of this research is to investigate digital-based problem based learning models for elementary school teacher education students. An important finding in this research is metacognitive awareness in problem based learning which is carried out on a digital basis, to facilitate the development of critical and creative thinking of prospective elementary school teachers. Problem based learning model to encourage student academic success. This research aims to develop an Android-based learning system to improve elementary school students' thematic learning. This research and development uses the simplified Borg and Gall model by Sukmadinata, which consists of preliminary studies, media development and media testing. The research subjects were fifth grade elementary school students in the Blora area, Central Java. Data collection was carried out using tests, questionnaires and interviews. The collected data was then analyzed qualitatively and quantitatively. Qualitative analysis uses the Miles and Huberman interactive model, while quantitative analysis uses a combined paired sample t test. The results of product testing for an Android-based thematic learning system report the value of the Paired Sample T Test. The signature for the post-test value is 0.012 < 0.05 or H0 is rejected. Thus, there is an influence of the use of the learning system in each study group on the consideration of student learning outcomes. So it can be concluded that the integrative thematic learning system developed is suitable for use by teachers and students in elementary schools to improve learning outcomes.Keyword: Thematic Learning System, Effective Learning Media, Elementary School